Reply to Comment by A. Argnani on "Geometry of the Deep Calabrian Subduction From Wide‐Angle Seismic Data and 3‐D Gravity Modeling". (29th July 2020) - Dellong, David; Klingelhoefer, Frauke; Dannowski, Anke; Kopp, Heidrun; Murphy, Shane; Graindorge, David; Margheriti, Lucia; Moretti, Milena; Barreca, Giovanni; Scarfì, Luciano; Polonia, Alina; Gutscher, Marc‐Andre
Key Points: This contribution is a reply on a comment submitted by A. Argnani The alternate interpretation of the wide‐angle seismic model is discussed The Alfeo Fault system is proposed to be the current location of STEP fault Abstract: Andrea Argnani in his comment on Dellong et al. (2020, https://doi.org/10.1029/2019gc008586 ) (Geometry of the deep Calabrian subduction (Central Mediterranean Sea) from wide‐angle seismic data and 3‐D gravity modeling) proposes an alternate interpretation of the wide‐angle seismic velocity models presented by Dellong et al. (2018, https://doi.org/10.1002/2017JB015312 ) and Dellong et al. (2020) and proposes a correction of the literature citations in these paper. In this reply, we discuss in detail all points raised by Andrea Argnani.